INVESTIGATION ON DRAG REDUCTION OF UNDERWATER GLIDER BY MANIPULATING THE ANGLE OG HEADING - MOHAMMAD , SYAFIQ AZYAN (2018)
Underwater glider had become popular choice for under water explorations by the scientist. Because of its advantage for long-term exploration. However underwater glider have low surge speed because underwater glider did not use propeller to move.